Design and manufacture the top head of a diesel furnace - Amirul Shazwan, Omar (2010)
Manufacturing technology is very important to people nowadays in making everyday items and industrial usage. Manufacturing technology grows faster because it is needed in human life. The diesel furnace is a furnace which melts non-ferrous metals for manufacturing purposes. The furnace burns metals with the source of diesel fuel which directed from the exhaust of the furnace. The melted products then poured in a mould which has been formed according to desired shape. This process called sand casting. Top head is one of important part in a diesel furnace. The purpose of the top head is to cover and close the furnace. It also helps to improve the burning performance while melting metals. The project starts with studies and research. From the information, designs created and only one of the designs will be selected from screening process. With the design, manufacturing process held. The processes involved are cutting, rolling, welding and plasma cutting. When the project finishes manufactured, it will be tested to determine the function and performance of the project. Any further problem and recommendation regarding the project is discussed on the last chapter.